Unraveling dimethylformamide-induced neutrophilic differentiation in HL-60 cells: A proteomic and functional comparison with dimethyl sulfoxide - Othman Eldalal; Yasser Tabana; Dinesh Babu; Newton H. Tran; Steven Lockhart; Joshua Kranrod; John M. Seubert; Lusine Tonoyan; Richard P. Fahlman; Arno G. Siraki (PLoS ONE, 2026)
The differentiation of HL-60 cells into neutrophil-like cells is widely used to study neutrophil functions, yet no comprehensive proteomic analysis has been conducted on dimethylformamide (DMF)-induced differentiation. This study provides the first detailed proteomic characterization of DMF-differentiated (df)-HL-60 cells, demonstrating its distinct molecular and functional profiles compared to the well-established dimethyl sulfoxide (DMSO)-df-HL-60 cell model. HL-60 cells were differentiated using 1.25% DMSO or 70 mM DMF for five days. Cell proliferation, granulocytic differentiation (CD11b expression), superoxide anion production, myeloperoxidase (MPO) protein expression and enzymatic activity, and neutrophil extracellular trap (NET) formation were evaluated. Proteomic profiling was performed using LC-MS/MS, followed by gene ontology and pathway enrichment analysis to identify key molecular changes associated with differentiation. DMF-df-HL-60 cells maintained higher proliferation rates than DMSO-df-HL-60 cells. Both agents successfully induced granulocytic differentiation, with DMSO producing greater CD11b expression. Functionally, both differentiation methods enhanced superoxide anion production, but DMF-df-HL-60 cells generated distinct superoxide radical spectra when evaluated with EPR spectroscopy. MPO protein expression and activity were significantly reduced in both differentiation models, indicating a transition to a mature neutrophil-like phenotype. Proteomic analysis revealed that neutrophil degranulation was the most significantly enriched pathway in DMF-df-HL-60 cells, alongside pathways involved in oxidant production and receptor tyrosine kinase signaling. Furthermore, S100 calcium-binding protein A9 (S100A9) abundance was significantly higher in DMF-df-HL-60 cells, suggesting a novel role of DMF in modulating neutrophil differentiation. DMF-df-HL-60 cells also showed activation of MAPK, Ras, and Rap1 signaling pathways, similar to the DMSO-df-HL-60 cell model, which is crucial for differentiation and immune responses. DMF-df-HL-60 cells generated more NETs than the DMSO-df-HL-60 cell model with phorbol myristate acetate. This study emphasizes the importance of selecting the appropriate differentiation model to accurately mimic neutrophil biology and highlights DMF’s unique role in neutrophil differentiation, providing novel insights into differentiation-induced functional adaptations.